2007
DOI: 10.1007/s10672-007-9035-1
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Privacy: Employee Relations and Legal Implications of Monitoring Employee E-mail Use

Abstract: The tradeoff between employees' workplace privacy and employers' need to protect company assets, safeguard proprietary information, and avoid costly litigation has been receiving increased attention (Lee and Kleiner 2003;Mello 2003; National Workplace Institute 2004). This tradeoff often favors employers, as the legal system provides much leeway for employers to monitor employees' electronic communications in the workplace. However, employers need to consider the effect such monitoring has on their employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…It could be contended that people living in environments in which intruders or unwanted visitors might access their privacy in the home without their consent could raise levels of anxiety among the affected individuals. Research has demonstrated that invasion of privacy results in the development of emotional disorders, such as anxiety disorders, mood disorders, stress or depression (Briere & Smiljanick, 1994;Demare, Briere, & Lips, 1988;Friedman & Reed, 2007;Hughes, 2004). Children living in unsecured dwellings could fear mugging, sexual assault, home invasion, or forced sex resulting in HIV infection, sexually transmitted diseases or unwanted pregnancies (Gordon, King, Gullone, Muris, & Ollendick, 2007).…”
Section: Limited Living Space and Emotional Disordersmentioning
confidence: 99%
“…It could be contended that people living in environments in which intruders or unwanted visitors might access their privacy in the home without their consent could raise levels of anxiety among the affected individuals. Research has demonstrated that invasion of privacy results in the development of emotional disorders, such as anxiety disorders, mood disorders, stress or depression (Briere & Smiljanick, 1994;Demare, Briere, & Lips, 1988;Friedman & Reed, 2007;Hughes, 2004). Children living in unsecured dwellings could fear mugging, sexual assault, home invasion, or forced sex resulting in HIV infection, sexually transmitted diseases or unwanted pregnancies (Gordon, King, Gullone, Muris, & Ollendick, 2007).…”
Section: Limited Living Space and Emotional Disordersmentioning
confidence: 99%
“…From a theoretical perspective, such a study will help formulate the ESI concerns. From a practical standpoint, such a study can help organizations alleviate legal liability claims arising due to employee privacy violation and can also foster better participation of employees in organizational activities with a view to enhancing their productivity and innovation [40,22]. Despite allusions in prior legal literature to concepts of spatial privacy, the discourse in the mainstream organizational literature on employee monitoring has not yet incorporated these key concepts.…”
Section: Conceptualizing Employee Spatial Intrusion (Esi): Accessibilmentioning
confidence: 99%
“…Previous studies have found that employees believe it is acceptable for management to monitor employees (Grant & Higgins, 1991;Oz, Glass, & Behling, 1999). However, other studies have argued that employers need to look beyond their legal rights and consider the adverse effects on employee morale when considering monitoring efforts, especially when monitoring personal conduct during break periods or activities outside the work environment (Friedman & Reed, 2007;Tolchinsky et al, 1981). When organizational monitoring activities are not directly related to performance, employees tend to perceive the monitoring as an invasion of privacy (Alder, 2001;Alder & Ambrose, 2005;Alge, 2001;Ambrose, Alder, & Noel, 1998).…”
Section: Employee Accountability Perceptionsmentioning
confidence: 99%
“…In early email system deployments, the privacy rights of employees with regard to employer-owned email systems were often unclear (Cappel, 1995;Oz et al, 1999). More recently, legal rulings have clearly favored the right of the employer to monitor email if they have reasonable business concerns for doing so (Friedman & Reed, 2007). However, Sipior and Ward (1995) assert that employees are likely to perceive email monitoring as invasive.…”
Section: Employee Accountability Perceptionsmentioning
confidence: 99%